Effects of fluoxetine on sex hormonal levels in depressed male patients - Imad A.J Thanoon; Ashraf Hashim Ahmed; Basel Mohamed All Aljalaby (University of Mosul, 2006)
Objective: This study was conducted to assess the effect of fixed dose fluoxetine monotherapy in depressed male patients on serum levels of testosterone, prolactin, follicular stimulating hormone (FSH), luteinizing hormone (LH) and estradiol. Subjects and methods: Twenty male patients with depression on 20 mg/day fluoxetine monotherapy and 20 apparently healthy male taken as a control group, were included in this study. Serum hormonal levels of testosterone, prolactin, FSH, LH, and estradiol were assesd in both patients on fluoxetine therapy and the control group, using special kits for each hormonal assay with the aid of Gamma Counter. Results: There were no significant differences in levels of testosterone, prolactine, FSH, LH, and estradiol between depressed male patients on fluoxetine therapy and controls. Conclusion: Fluoxetine therapy in a dose of 20 mg/day can be considered as a safe antidepressant drug on serum levels of testosterone, prolactin, FSH, LH and estradiol.